2005
DOI: 10.1002/jsfa.2103
|View full text |Cite
|
Sign up to set email alerts
|

Improving the quality of sorghum injera by decortication and compositing with tef

Abstract: Injera is an Ethiopian fermented pancake-like bread made from cereals, with tef being preferred. Decortication and compositing with tef were evaluated as methods to improve the injera-making quality of red tannin-free and tannin-containing sorghums. Both decortication and compositing improved sorghum injera quality. Concerning decortication, mechanical abrasion was found to be more effective than hand pounding because acceptable injera was obtained with lower milling loss. Good quality injera was produced at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 14 publications
4
46
1
Order By: Relevance
“…Similarly the effect of flour mean particle size was important (p < 0.05 and r = −0.5 to −0.6) on gel hydration properties of the tef flours and this could be due to higher surface area being exposed for water binding. Earlier work by Yetneberk et al (2005) shows that in sorghum and tef composite flours the WSI increased progressively with increasing proportion of tef, giving injera better quality. The increase in WSI agreed with the observation that, during mixing, compared with sorghum, tef dough tended to be stickier and water-soluble components in the tef flour could have modified the dough rheology and the texture of injera positively (Yetneberk et al, 2005).…”
Section: Varietymentioning
confidence: 95%
See 2 more Smart Citations
“…Similarly the effect of flour mean particle size was important (p < 0.05 and r = −0.5 to −0.6) on gel hydration properties of the tef flours and this could be due to higher surface area being exposed for water binding. Earlier work by Yetneberk et al (2005) shows that in sorghum and tef composite flours the WSI increased progressively with increasing proportion of tef, giving injera better quality. The increase in WSI agreed with the observation that, during mixing, compared with sorghum, tef dough tended to be stickier and water-soluble components in the tef flour could have modified the dough rheology and the texture of injera positively (Yetneberk et al, 2005).…”
Section: Varietymentioning
confidence: 95%
“…Earlier work by Yetneberk et al (2005) shows that in sorghum and tef composite flours the WSI increased progressively with increasing proportion of tef, giving injera better quality. The increase in WSI agreed with the observation that, during mixing, compared with sorghum, tef dough tended to be stickier and water-soluble components in the tef flour could have modified the dough rheology and the texture of injera positively (Yetneberk et al, 2005). In evaluating injera making potentials of sorghum varieties higher WSI gave more fluffy, soft and rollable injera (Yetnebrerk, 2004).…”
Section: Varietymentioning
confidence: 95%
See 1 more Smart Citation
“…The same report also indicated that sensory quality differences are governed mainly by varietal inherent differences with less impact from environmental factors. Yetneberk et al (2005) also reported that decortication of sorghum and compositing with tef improved injera quality. In the study of injera made from tef, Parker et al (1989) reported that tef starch played a major role in the formation of injera surface gas holes.…”
Section: Resultsmentioning
confidence: 95%
“…This is due to its softer texture, preferred taste and colour (Yetneberk et al, 2005;Abraha et al, 2013). Normally, injera with uniformly distributed surface gas holes, soft plumpness, non-sticky and having slightly sweet taste is commonly preferred by injera consumers (Abraha et al, 2013).…”
Section: Introductionmentioning
confidence: 99%